Laparoscopic retroperitoneal necrosectomy in patients with necrotizing pancreatitis: addressing the limitations of traditional treatment options - Jinjian Li; Zihao Huang; Bo Shen; Hong Yu (BMC Gastroenterology)
Abstract Background Laparoscopic retroperitoneal necrosectomy (LRN) is a novel minimally invasive approach for treating infected necrotizing pancreatitis. Our study aims to evaluate the safety and effectiveness of LRN for pancreatic necrosis at a single center. Methods This retrospective study analyzed 120 patients who had laparoscopic retroperitoneal necrosectomy (LRN) for necrotizing pancreatitis at Sir Run Run Shaw Hospital from November 2017 to May 2023, with a six-month follow-up. Patients included had no prior surgeries. We evaluated the incidence of postoperative complications and mortality rates. Furthermore, subgroup analyses were performed to assess mortality and complications, utilizing univariate and multivariate regression analyses to identify associated risk factors. Results Among the 120 patients, complications classified as Clavien-Dindo grade ≥ III occurred in 34.2%, and 8.3% experienced surgery-related mortality. In the multivariate regression analysis of complications classified as Clavien-Dindo grade ≥ III, length of stay (LOS) in the ICU (OR = 1.026;95% confidence interval [CI], 1.005 to 1.047; P = 0.015), and the presence of extrapancreatic infections (OR = 3.656;95% confidence interval [CI], 1.443to 9.261; P = 0.006) were identified as risk factors. A total of 77 patients with severe acute pancreatitis (according to the modified Atlanta classification) were included in the study. After 48 h of treatment, the SOFA score significantly decreased (5.92 ± 4.56 vs. 4.06 ± 3.44; P < 0.01), and the CT severity index (CTSI) also significantly decreased at one week post-surgery (7.57 ± 2.29 vs. 6.23 ± 2.28; P < 0.01). CRP levels (144.34 ± 77.45 vs. 87.94 ± 67.63; P < 0.01) and WBC count (10.97 ± 6.84 vs. 9.95 ± 6.79; P = 0.048) significantly decreased within one week after surgery. Among the 23 patients with preoperative hemodynamic instability, 13 required only a single surgery, while 4 required conversion to open surgery. At 48 h post-surgery, the SOFA score significantly decreased (8.74 ± 5.71 vs. 6.17 ± 4.94; P = 0.021), and the CTSI at one week was also considerably lower (8.26 ± 2.03 vs. 6.78 ± 2.04; P < 0.01). Conclusion LRN allows over 70% of patients to avoid multiple surgeries while achieving excellent therapeutic outcomes. Furthermore, it is particularly effective for critically ill patients with hemodynamic instability, offering a distinct advantage over alternative treatments. Thus, LRN represents a promising therapeutic approach deserving of broader adoption.